Contribution of Reynolds shear stress to near-wall turbulence in Rayleigh–Bénard convection. (December 2021) - Ahn, Junsun; Kim, Ki-Ha; Pan, Xiaomin; Choi, Jung-Il
Highlights: Direct numerical simulations of turbulent Rayleigh-Bénard convection are performed. Short-time averaged velocity gradient productions show near-wall intensive peaks. Near-wall Reynolds shear stress correlates strongly with velocity shear. These correlations result in the velocity-gradient production. Anisotropic Reynolds stresses behave similarly to a canonical turbulent channel flow. Abstract: Direct numerical simulations of Rayleigh–Bénard convection flows are performed for P r = 0.7 with R a = 5 × 10 8 and 2 × 10 10, and for P r = 0.021 with R a = 10 7 and 5 × 10 8, where P r and R a are the Prandtl number and the Rayleigh number, respectively. The velocity-gradient production based on the short-time averaging shows the near-wall intensive positive peak and negative region. The correlations between the Reynolds shear stresses and the wall-normal and transverse gradients of the horizontal mean velocities locally and temporally result in the positive and negative velocity-gradient production near the wall. The eigenvalues of the anisotropic Reynolds stress tensors on the barycentric map show that the short-lived anisotropy related to the one-directional stretching occurs along the wall-normal distance; this behavior is similar to that of a canonical turbulent channel flow. The results indicate that the local and temporal Reynolds shear stresses near the wall with the shear of the horizontal mean velocities play an important role in the near-wall velocity-gradient production, which leads to the turbulent regime in the Rayleigh–Bénard convection flow with an increase in Rayleigh number.